SEX AND SEXUALITY: AN ANALYSIS OF THE GENDER PARADIGM UNDER THE SOCIAL CONCEPT APPROACH AND THE IDENTITY ANALYSIS OF THE TRANS PERSON (Anais do Congresso Brasileiro de Processo Coletivo e Cidadania, 2023)
Transsexuality is a subject that has been dealt with for a long time by the Courts, and with the Right of Biodiversity this problem comes to light by the circumstances and evolution of society. Discrimination based on the option of sexual orientation or gender identity refers to any distinction, exclusion, restriction or preference based on sexual orientation or gender identity that seeks to harm equality before the legal system and its protection, recognition, enjoyment, The exercise of an equal form of any fundamental right and guarantee Such discrimination of gender identity or sexual orientation is usually aggravated by prejudices based on other circumstances, especially those related to gender, creed, ethnicity, social and financial conditions. . Keywords: Gender; Transsexuality; Sexuality.